O surrealismo em As metamorfoses de Murilo Mendes - Santos, Felipe Neiva dos (2012)
The following study investigates the presence of Surrealism in the book As metamorfoses, published in 1941. Firstly, this study presents a review of French Surrealism, whose ideology contains the senses of imagination, dream, wonderful, collection, etc. Thus, we seek to identify both the main features of the movement, as well as their limitations and contradictions. Secondly, the book As metamorfoses is analysed in its relationship with the surrealist poetry, especially the notion of fusion of opposites, present both in the French movement and the Brazilian poet. However, our goal is not to classify the poet as a Surrealist, but rather identify both the impact and consequences of the French movement in the work of Murillo, and the peculiarities and differences of a great poet